Genomics of elite sporting performance: what little we know and necessary advances - Pitsiladis, Y.; Wang, G.; Wolfarth, B.; Scott, R.; Fuku, N.; Mikami, E.; He, Zi.; Fiuza-Luces, C.; Eynon, N.; Lucia, A. (British Journal of Sports Medicine, 2013)
Numerous reports of genetic associations with performance-related phenotypes have been published over the past three decades but there has been limited progress in discovering and characterising the genetic contribution to elite/world-class performance, mainly owing to few coordinated research efforts involving major funding initiatives/consortia and the use primarily of the candidate gene analysis approach. It is timely that exercise genomics research has moved into a new era utilising well-phenotyped, large cohorts and genome-wide technologies—approaches that have begun to elucidate the genetic basis of other complex traits/diseases. This review summarises the most recent and significant findings from sports genetics and explores future trends and possibilities.